2009
DOI: 10.1007/s00280-009-1029-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of UGT2B7 and ABCB1 genotypes with morphine-induced adverse drug reactions in Japanese patients with cancer

Abstract: Our findings suggest that pharmacogenetics can be used to predict the risk of morphine-induced adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…A higher frequency of opioid-related adverse events such as sweating and sedation was reported in 3435TT genotyped individuals receiving remifentanil for spinal fusion surgery (33 ). Other SNPs in ABCB1, 1236CϾT (rs1128503) and 2677GϾT/A (rs2032582), have also been found to be related to adverse events (26,32,34,35 ). Other studies, including one in a pediatric population, could not confirm this increased risk for adverse events in carriers of the 3435T allele [see online Supplemental Table 3; ABCB1, references…”
Section: Abcb1mentioning
confidence: 96%
See 1 more Smart Citation
“…A higher frequency of opioid-related adverse events such as sweating and sedation was reported in 3435TT genotyped individuals receiving remifentanil for spinal fusion surgery (33 ). Other SNPs in ABCB1, 1236CϾT (rs1128503) and 2677GϾT/A (rs2032582), have also been found to be related to adverse events (26,32,34,35 ). Other studies, including one in a pediatric population, could not confirm this increased risk for adverse events in carriers of the 3435T allele [see online Supplemental Table 3; ABCB1, references…”
Section: Abcb1mentioning
confidence: 96%
“…Adult Japanese patients (n ϭ 32) carrying the UGT2B7*2 allele reported less nausea while on oral morphine therapy for cancer pain than did patients carrying the wild-type UGT2B7 allele (26 ). However, not all clinical studies found an effect of these UGT2B7 polymorphisms on morphine PK or PD [see online Supplemental Table 3; UGT2B7, references (1-4 )].…”
Section: Ugt2b7mentioning
confidence: 99%
“…P-glycoprotein (P-gp), the product encoded by ABCB1 gene, is a member of the ATP-binding cassette (ABC) transporter superfamily (Chen et al, 1986). As an ATP-dependent transmembrane efflux pump, it has been closely linked to resistance to substrates including opioids prevented from transporting across the blood-brain barrier to decrease analgesia action in the central nervous system (CNS) (Zhou et al, 2007;Fujita et al, 2010;Fernandez et al, 2012). The pain relief of morphine and fentanyl were much better in P-gp deficient mice than wild type (WT) (Hamabe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms underlying this variability can help identify susceptible patient populations. Opioid-related adverse events occur in approximately 15% of postoperative patients in the clinical setting (Kessler et al, 2013) and represent a subset of VDRs that may be attenuated by considering altered function of opioid metabolizing enzymes and transporters (Fujita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%